ETHNOMATHEMATICS VALUES IN SUMEDANG TOFU AND BONGSANG (TOFU BASKET) FOR TEACHING GEOMETRY IN PRIMARY SCHOOL - Riana Irawati; Rahman Rahman; Retno Andriyani; Ejen Jenal Mutaqin; Nurdin Kamil (FKIP Universitas Muhammadiyah Tangerang, 2023)
Ethnomathematics can be an option for teaching a more contextual mathematics which contributes to a successful mathematics learning. The present study highlighted ethnomathematics concepts that could be found in Sumedang’s local food, namely Sumedang Tofu, and the bamboo basket used as its container (bongsang). Mathematical concepts in Sumedang Tofu and its bongsang are related to geometry. Geometry allows students to develop their abilities in presenting or describing the order in the world or their immediate environment. Geometry learning affects students’ ability to connect mathematical ideas, both in the discipline and to other disciplines as well as the real world. The results of this study show that Primary School students still had difficulties in learning and understanding geometry. Therefore, it was necessary to develop a method that would improve students’ understanding of geometrical concepts, which were important because they were highly relevant to students’ daily life. The present study aimed to explore geometrical concepts found in Sumedang tofu and bongsang. Descriptive qualitative approach was implemented, in which the data was gathered through observation, literature study, and interviews. The findings indicated that geometrical concepts could be found in Sumedang tofu and bongsang. Those concepts could be used in mathematics lessons in primary school to provide meaningful learning for students. The results of this study could be used as a foundation to develop an ethnomathematics learning in primary school level.